Optimization of a synthetic jet actuator for flow control around an airfoil - Montazer, Elham; Mirzaei, Masoud; Salami, Erfan; Ward, Thomas Arthur; Romli, Fairuz Izzudin; Kazi, Salim Newaz (IOP Publishing, 2016)
This paper deals with the optimization of a synthetic jet actuator parameters in the control flow around the NACA0015 airfoil at two angles of attack: 13° (i.e. the stall angle of NACA0015) and 16° (i.e. the post stall angle of NACA0015) to maximize the aerodynamic performance of the airfoil. Synthetic jet actuator is a zero mass flux-active flow control device that alternately injects and removes fluid through a small slot at the input movement frequency of a diaphragm. The movement of the diaphragm and also the external flow around the airfoil were simulated using numerical approach. The objective of the optimization process function was maximum lift-drag ratio (L/D) and the optimization variables were jet frequency, length of the jet slot and jet location along the chord. The power coefficient of the jet was considered as a constraint. The response surface optimization method was employed to achieve the optimal parameters. The results showed that the actuator is more effective for post stall angles of attack that can lead to an enhancement of 66% in L/D.